Towards Code-centric Code Generators - Busch, Daniel (Electronic Communications of the EASST, 2023)
This paper presents a novel approach to code generation. While common code generator approaches lack in support for code evolution and maintenance such as refactoring, the presented Code-centric generator (CCG) approach attempts to overcome these issues. Instead of mixing generator abstractions and actual code snippets, CCG provides a layer between the generator and prototypical target code. The new layer provides the ability to map code generator operations directly onto code AST subtrees, and generates the resulting generators based on these mappings and the prototypical target implementation.